Dynamic capabilities and family businesses: a perspective article (2024)
The individual perspective of dynamic capabilities and family firms could be useful to shed light on the relationship between these topics, considering not only the heterogeneity of family businesses but above all the diversity of their collaborators, highlighting the underlying elements through which these firms are sustained. Design/methodology/approach: This paper is based on systematic research, considering the most relevant literature about dynamic capabilities and family firms. Findings: Findings highlight the individual perspective of dynamic capabilities and family firms, where we identify the main elements that family businesses must be aware of to be more innovative: high knowledge management/social capital, high entrepreneurial mindset/orientation, high tradition (retrospective and prospective), high empowering leadership, high next generation involvement, extended SEW (long-term perspective), risk-neutral, low conservative/inertia/paternalism and low emotionally attached. Originality/value: The paper analyzes relevant studies on dynamic capabilities and family firms, proposing a research agenda with questions for further inquiries that cover inertia, paternalism, digital transformation and the individual perspective of dynamic capabilities and family firms. In addition, the authors provide practical implications for these topics.